Perancangan Aplikasi Pengelolaan Rumah Tangga Laboratorium Komputer STT-PLN - Rizqia Cahyaningtyas; Awit Lela Sigi (KILAT, 2015)
PLN STT campus Department of Information Engineering have 5 computer labs, each of which has a different function so that the needs of households and any inventory each has different needs as well, but will need to be especially household applications required by the all the computer labs are broadly have the same needs: managing demand for goods, equipment and laboratory equipment, household budget until the correspondence. Where at the moment the data needs of households still created and stored using Microsoft Word and Microsoft Excel because of the perceived lack of effective then the author will make the application more household management automatically so as to facilitate and speed up the process of calculation of the household budget, manufacture of correspondence, filing goods and storage of data and information. So it is expected that these applications can help the process of managing the household of computer laboratories in order to more effectively and efficiently.